Prevalence and Risk Factors of Obesity and Hypertension Among University Students in Rajshahi City, Bangladesh (Bangladesh Pharmaceutical Journal, 2016)
Obesity has become a new challenge for health care providers in the world, which leads to reduced life expectancy or increased health problems. The aim of the present study was to assess the prevalence and risk factors of obesity and hypertension among the undergraduate and postgraduate students in Rajshahi city. About 675 students were interviewed by standard questionnaires with their verbal consents. In this study, we found that a major portion of the population (13.93% which is about 94 students out of 675) were overweight and 61 students (9.04%) were obese at different stages on the basis of Body Mass Index (BMI) values where 75.41% and 31.15% were male and female students, respectively. About 31.15% of the obese students came from families with monthly income of 31000-40000 taka and 29.50% obese students have at least one obese parent. We also observed that about 32 students (52.46%) out of 61 obese students were pre-hypertensive and 34.43% obese students were stage I hypertensive patient. In this study, we found that the most common risk factors of obesity and hypertension among university students were sedentary life style, physical activity less than 30 min/day, smoking, frequent intake of soft drinks, fast food and food rich in fats (Junk food). This may be the first health survey conducted regarding obesity and hypertension among these university students in Bangladesh, which might be helpful for health workers to raise awareness among the mass people.Bangladesh Pharmaceutical Journal 19(2): 179-184, 2016